Commuting Accidents Within Construction Sectors: A Review of Case. Issue 1 (May 2020) - Sukor, E S A; Suratkon, A; Mohammad, H
Abstract: Road traffic accidents are the leading cause of death in most countries, and the eighth leading cause of death worldwide. In Malaysia, this situation is particularly alarming when data obtained from the Road Safety Department shows an increase in the number of road accidents over time. Zooming in to accidents involving employees working in organizations, a major concern emerged since a recent statistic from the Social Security Organization (SOCSO) of Malaysia shows that accidents reported to SOCSO increased from 61, 552 cases in 2012 to 69, 980 cases in 2017. Although covering both industrial and commuting accidents, SOCSO's data on the latter for the construction sector recorded a total of 1, 913 accidents in 2012 and continues to increase dramatically to 3, 386 accidents in 2016, which among the highest within all industry sector. Defined as an accident while travelling back and forth to official business (from or to the workplace), previous data on commuting accidents for one of the nation's crucial sector are further dampened the existing negative image of safety in construction. Furthermore, this issue has resulted in an increase in mortality, an extensive compensation claims, and losing valuable talent. Thus, following the hard-cold data presented by the paper, an initiative for a full-fledge research undertaking are in the pipeline. This to ensure a holistic solution for the problem in hand and ensuring improvement for safety and health of construction personnel particularly during commuting.